2022
DOI: 10.1186/s13287-022-03151-0
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide of Enterococcus faecium L15 promotes the osteogenic differentiation of human dental pulp stem cells via p38 MAPK pathway

Abstract: Background Bone has important functions in the body. Several researchers have reported that the polysaccharides and lipopolysaccharide derived from microbes can promote osteogenic differentiation of stem cells. Enterococcus faecium, a lactic acid bacterium (LAB), produces several bioactive metabolites and has been widely applied in the food and nutraceutical industries. The exopolysaccharide (EPS) from LAB has also been extensively examined for its postbiotic effects and for its in vivo and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…It has also been shown that L. rhamnosus GG rescues the proliferation and osteogenic differentiation of mandible‐derived mesenchymal stem cells (MMSCs) and thereby protects against mandibular bone loss (induced by tenofovir) in mice. The Kim et al study demonstrated that Enterococcus faecium L15 exopolysaccharide enhances the osteogenesis of human dental pulp stem cells through the p38 MAPK signaling pathway 76 .…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that L. rhamnosus GG rescues the proliferation and osteogenic differentiation of mandible‐derived mesenchymal stem cells (MMSCs) and thereby protects against mandibular bone loss (induced by tenofovir) in mice. The Kim et al study demonstrated that Enterococcus faecium L15 exopolysaccharide enhances the osteogenesis of human dental pulp stem cells through the p38 MAPK signaling pathway 76 .…”
Section: Resultsmentioning
confidence: 99%
“…However, LPS at a concentration of 10 µg/ml significantly inhibited the osteogenic differentiation of hPDLSCs, which was in line with the findings of several previous studies [ 16 , 26 , 27 ]. Notably, the effects of LPS on cell osteogenic differentiation could differ based on the concentration of LPS because several previous studies reported that low concentrations of LPS (less than 1 µg/ml) had a positive effect on the osteogenesis of stem cells in vitro [ 24 , 25 , 28 30 ]. Considering that there may be a large amount of residual LPS in the periodontal tissues of patients with periodontitis, it is still necessary to protect hPDLSCs from the potential negative effects of LPS on osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, although we identified that resistin targeted TAZ to induce OD through PI3K/AKT/mTOR pathway, the crosstalk with other signaling pathways cannot be ruled out, and the interaction between resistin and the OD-related genes remains to be further revealed. We next sought to explore other possible pathways, including Wnt/β-catenin pathway 42 , 43 and MAPK pathway, 44 , 45 and carry out relevant clinical studies. Secondly, bone defect remodeling is a dynamic process involving osteogenesis (bone formation) and osteoclastogenesis (bone resorption).…”
Section: Discussionmentioning
confidence: 99%